Transgender Victims and Offenders: Failures of the United States Criminal Justice System and the Necessity of Queer Criminology - Buist, Carrie L. (Critical criminology, 2014)
The purpose of this article is to highlight the experiences of transgender people within the criminal justice system as both victims and offenders. We contend that queer criminology is both needed and can assist in exploring the experiences of this unique population who face discrimination within the US criminal justice system and who are often ignored within criminological research. The article will provide an overview of transgender people’s general experiences within the criminal justice system and explore influences of cultural stereotypes about transgender people by examining the cases of three transgender victims of violence—Brandon Teena, Gwen Araujo, and Cece McDonald. This article highlights the importance of concepts such as sex, gender, transpanic, transphobia, victim-blaming, and the responses by key players in the criminal justice system (police, courts, and corrections) to transgender victims and offenders.